Pengaruh jenis proses pemotongan pada mesin milling terhadap getaran dan kekasaran permukaan dengan material aluminium 6061 - Okky Nugra Retyawan; Indri Yaningsih; Heru Sukanto (Jurnal Teknik Mesin Indonesia, 2017)
This research was aims to determine the effect of the cutting process type on a milling machine to vibration and surface roughness of the aluminum 6061. The specimens were made using a cutting process type face milling, profile milling, pocket milling, slot milling and drilling. Surface roughness data retrieval is done on any type of cutting process using a surface roughness tester and vibration data was taken during a cutting process on any cutting process type using a vibration meter. The results showed the value of surface roughness and vibration in face milling of 0,5368 μm and 1,03 m/s², profile milling of 1,0984 μm and 1,49 m/s², pocket milling of 1,1004 μm and 1,73 m/s², slot milling of 1,4888 μm and 2,44 m/s² and drilling of 1,9944 μm and 18,62 m/s². Cutting process type on a milling machine having an influence on the vibrations and surface roughness. Each cutting process type has a different cutting force. The greater the cutting force that occurs in every cutting process type, the greater the value of the vibration and the surface roughness happened.